Neural differentiation of transplanted neural stem cells in a rat model of striatal lacunar infarction: light and electron microscopic observations - Muñeton-Gomez, Vilma C.; Doncel-Perez, Ernesto; Fernandez, Ana Patricia; Serrano Masa, Julia; Pozo-Rodrigalvarez, Andrea; Vellosillo-Huerta, Lara; Scott Taylor, Julian; Cardona-Gomez, Gloria Patricia; Nieto-Sampedro, Manuel; Martinez-Murillo, Ricardo (Frontiers in Cellular Neuroscience, 2012)
The increased risk and prevalence of lacunar stroke and Parkinson's disease (PD) makes the search for better experimental models an important requirement for translational research. In this study we assess ischemic damage of the nigrostriatal pathway in a model of lacunar stroke evoked by damaging the perforating arteries in the territory of the substantia nigra (SN) of the rat after stereotaxic administration of endothelin-1 (ET-1), a potent vasoconstrictor peptide. We hypothesized that transplantation of neural stem cells (NSCs) with the capacity of differentiating into diverse cell types such as neurons and glia, but with limited proliferation potential, would constitute an alternative and/or adjuvant therapy for lacunar stroke. These cells showed neuritogenic activity in vitro and a high potential for neural differentiation. Light and electron microscopy immunocytochemistry was used to characterize GFP-positive neurons derived from the transplants. 48 h after ET-1 injection, we characterized an area of selective degeneration of dopaminergic neurons within the nigrostriatal pathway characterized with tissue necrosis and glial scar formation, with subsequent behavioral signs of Parkinsonism. Light microscopy showed that grafted cells within the striatal infarction zone differentiated with a high yield into mature glial cells (GFAP-positive) and neuron types present in the normal striatum. Electron microscopy revealed that NSCs-derived neurons integrated into the host circuitry establishing synaptic contacts, mostly of the asymmetric type. Astrocytes were closely associated with normal small-sized blood vessels in the area of infarct, suggesting a possible role in the regulation of the blood brain barrier and angiogenesis. Our results encourage the use of NSCs as a cell-replacement therapy for the treatment of human vascular Parkinsonism.